Elimination of shallot bulb viruses through heat treatment - Margo Sulistio; Endang Sulistyaningsih; Siti Subandiyah (Universitas Gadjah Mada, 2015)
Shallot (Allium cepa L. Aggregatum group) is usually cultivated vegetatively. As a result, viruses tend to accumulate within the host plants and spread to healthy plants every crop cycle, reducing yield and bulb quality. There are a very limited number of studies about the elimination of shallot viruses through heat treatment. The objective of this research was to eliminate shallot viruses through heat treatment to produce virus-free plantlets. The leaves of Biru Lancor with specifc visual virus symptoms were detected by Reverse Transcription–Polymerase Chain Reaction (RT-PCR). Then bulbs of Biru Lancor that were positively infected by viruses were used as materials for heat treatment. The treatments were a control (without treatment), electric treatment at 15 mA for 10 minutes, heat treatment in an incubator at 37°C for 4 weeks, heat treatment in a waterbath at 45°C for 60 minutes, and combination of heat treatment in an incubator at 37°C for 4 weeks and heat treatment in a waterbath at 45°C for 60 minutes. After being subjected to heat treatment, the pseudo stem were cultivated in the MS Medium + 1 mg/L BAP + 1 mg/L IBA.Virus detection by RT-PCR was conducted 28 days after planting using samples of leaves from each plantlet. The results of this research showed that the treatments of electric treatment at 15 mA for 10 minutes and combination of heat treatment in the incubator at 37°C for 4 weeks and heat treatment in the waterbath at 45°C for 60 minutes could suppress the incidence of Shallot latent virus (SLV) until 100%. Heat treatment might have an important role in the degradation of virus particles by boosting Virus-Induced Gene Silencing (VIGS) as plant responses to virus infection.